Visible Light Communication and Positioning - Gong, Chen (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
In recent years, wireless communications have significantly evolved due to the advanced technology of smartphones;, portable devices; and the rapid growth of Internet of Things, e-Health, and intelligent transportation systems . Moreover, there is anare increasing need fors of emerging intelligent services like positioning and sensing in athe future intelligence society. Recent years have witnessed the growing research interests and activities in the communication and intelligencet services in the optical wireless spectrum, as a complementary technology to more